HIRING, CAREER, SALARY, AND WORKING HOURS FOR EDUCATION PROFESSIONALS IN SÃO PAULO STATE (1995-2018) - Barbosa, Andreza; Jacomini, Márcia Aparecida; Fernandes, Maria José da Silva [UNESP]; Venco, Selma (FapUNIFESP (SciELO), 2022)
The article examines forms of hiring and designation, career, working hours, and salaries of the education professionals’ group – teachers, coordinating teachers, school principals, teaching supervisors, and administration fonctionnaires – linked to the São Paulo State Department of Education in the period between 1995 to 2018. Based on extensive documentary research and analysis of statistical data, it’s possible to verify a strong adherence, in the various mandates, to the intrinsic values of the New Public Management, which, according with business practices, promoted flexibility in labor relations, reconfiguring educational, and not complying with national laws, such as the Law on the National Teaching Salary Floor.
CONTRATACIÓN, CARRERA, SALARIO Y JORNADA DE LOS PROFESIONALES DE LA EDUCACIÓN DEL ESTADO DE SÃO PAULO (1995-2018)
CONTRATAÇÃO, CARREIRA, VENCIMENTO E JORNADA DOS PROFISSIONAIS DA EDUCAÇÃO ESTADUAL PAULISTA (1995-2018)
Keywords: Educational politics; Employment contract; New Public Management; State education of São Paulo; Work conditions